ANALISIS WILLINGNESS TO PAY (WTP) RETRIBUSI PENGELOLAAN SAMPAH DI KECAMATAN CILEUNYI, KABUPATEN BANDUNG - Ruth Roselin Nainggolan (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
This study aims to analyze the value of Willingnes to Pay (WTP) and the factors that influence the value of WTP to waste management retribution into compost. This research was conducted in Cileunyi District, Bandung Regency, West Java Province. Cileunyi District is estimated to produce garbage reaching 330 m3 per day or 115 tons/ day. The number of samples is 96 families, calculated by the Frank Lynch formula. To find out the factors that influence WTP, use the correlation test, ANOVA test and multiple linear regression analysis using SPSS 24 software. Contingent Valuation Method (CVM) is used to analize the value of Community’s Willingness to Pay the retribution. The results of the study obtained as follows: age, level of education, income and number of family members together (simultaneous) affect the Willingness to Pay (WTP), the influence of all factors is 39.9%, the number of family members does not significantly affect the WTP, the average value of waste retribution paid is Rp. 10,208,33 and the average value of WTP for waste management into compost or recycled is Rp. 20,572.92.